Localizing Value of the Signs and Symptoms of Posterior Circulation Infarctions: A Logistic Regression Analysis. Issue 2 (December 2019) - Pazdera, Ladislav; Vysata, Oldřich; Kukal, Jaromir; Tran, Quang Van; Mojzes, Matej; Caplan, Louis Robert
Abstract: Introduction: Anatomical localization of brain infarcts based on clinical symptoms and signs is a key step in stroke diagnosis, but evidence linking specific clinical features with infarct locations is limited. We aimed to identify symptoms and signs of ischemic events that statistically favor precise posterior circulation locations. Patients and Methods: We analyzed data from the New England Medical Center Posterior Circulation Registry for 407 adults with previous posterior circulation ischemia (confirmed by brain/vascular imaging). Using multivariate logistic regression and the binary sorting table method, we determined the negative and positive predictive values of 24 signs and symptoms for infarct localization within the proximal, middle, or distal posterior circulation territories. Results: Visual field defect (hemianopia) was a positive or negative sign for all 3 brain stem regions. The presence of visual field defect positively correlated only with the distal region ( P < .001), and its absence indicated infarction in the proximal ( P = .007) or middle ( P < .001) territories. Visual field defect showed the greatest localizing sensitivity and specificity with other signs: visual field defect absence with presence of nausea−vomiting for the proximal region, or hemiparesis and other motor signs in the middle region; presence of visual field defect alone or with absence of generalized weakness in the distal region. Discussion and Conclusion: Presence of visual field defect alone statistically confirms the occurrence of a distal region infarct and excludes proximal or middle territory involvement. Moreover, presence or absence of this sign in the presence of other signs or symptoms localizes the event to proximal or middle regions.